Microsyntenic Clusters Reveal Conservation of lncRNAs in Chordates Despite Absence of Sequence Conservation - Carlos Herrera-Úbeda; Marta Marín-Barba; Enrique Navas-Pérez; Jan Gravemeyer; Beatriz Albuixech-Crespo; Grant N. Wheeler; Jordi Garcia-Fernàndez (Biology, 2019)
Homologous long non-coding RNAs (lncRNAs) are elusive to identify by sequence similarity due to their fast-evolutionary rate. Here we develop LincOFinder, a pipeline that finds conserved intergenic lncRNAs (lincRNAs) between distant related species by means of microsynteny analyses. Using this tool, we have identified 16 bona fide homologous lincRNAs between the amphioxus and human genomes. We characterized and compared in amphioxus and Xenopus the expression domain of one of them, Hotairm1, located in the anterior part of the Hox cluster. In addition, we analyzed the function of this lincRNA in Xenopus, showing that its disruption produces a severe headless phenotype, most probably by interfering with the regulation of the Hox cluster. Our results strongly suggest that this lincRNA has probably been regulating the Hox cluster since the early origin of chordates. Our work pioneers the use of syntenic searches to identify non-coding genes over long evolutionary distances and helps to further understand lncRNA evolution.